2013
DOI: 10.3389/fpsyt.2013.00117
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure and Addiction

Abstract: What is the role and value of pleasure in addiction? Foddy and Savulescu (1) have claimed that substance use is just pleasure-oriented behavior. They describe addiction as “strong appetites toward pleasure” and argue that addicts suffer in significant part because of strong social and moral disapproval of lives dominated by pleasure seeking. But such lives, they claim, can be autonomous and rational. The view they offer is largely in line with the choice model and opposed to a disease model of addiction. Foddy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
2
24
0
2
Order By: Relevance
“…The study methodology and some of the main findings are discussed elsewhere (see Snoek et al 2012;Horstkötter and Snoek, 2013;Kennett et al 2013;Kennett, Vincent and Snoek, 2014). In short, our research has revealed that we need a more layered concept of agency to understand how addiction impairs agency.…”
Section: Current Views On Substance Dependency and Agencymentioning
confidence: 94%
“…The study methodology and some of the main findings are discussed elsewhere (see Snoek et al 2012;Horstkötter and Snoek, 2013;Kennett et al 2013;Kennett, Vincent and Snoek, 2014). In short, our research has revealed that we need a more layered concept of agency to understand how addiction impairs agency.…”
Section: Current Views On Substance Dependency and Agencymentioning
confidence: 94%
“…Two types of rewarding systems are involved: 1) one for quitting drug abuse that activates behaviors that are necessary for life such as feeding, and 2) the other is the rewarding system that causes relapse due to adverse effect on mesolimbic dopaminergic system. 17 Exercise results in enhancement of neurogenesis, angiogenesis, and neuroplasticity, which in turn reduces side effects caused by drug abuse. 18 Another study shows overall enhancement in neurogenesis, angiogenesis, and neuroplasticity, and this shows that one possible reason such as angiogenic factor can result in enhancement of all of them.…”
Section: Discussionmentioning
confidence: 99%
“…As addiction develops, the drug-taking outcome, either actual or expected, becomes overvalued . This overvaluation can be a result of drug withdrawal (Hutcheson et al 2001), or an inflated expectation of the euphoric effects of the drug, even when the euphoric event is actually decreased in magnitude (Kennett et al 2013). Overvaluation of the drug-taking outcome ( O ) can lead to pathological drug-seeking ( A ), especially when triggered by drug cues ( S ).…”
Section: Addiction As a Disorder Of Learning And Decision Makingmentioning
confidence: 99%